A Form of Accountability CV Sumber Berkat Makmur Which Encroached On Customary Forests - Angga, La Ode; Labetubun, Muchtar Anshary Hamid; Fataruba, Sabri (SASI, 2023)
Introduction: The people of Sabuai Village reject the existence of a company that has been operating since 2019 Until now, the Environment Agency has never processed documents, either Amdal or other environmental documents according to the acting Head of the Maluku Province Environment Area. The people of Sabuai Village deny the existence of a company that has been operating since 2019, because it is suspected of cutting down and managing customary forest products without permission.Purposes of the Research: The long goal is to find out the Form of Accountability of CV Sumber Berkat Makmur that Encroaches on Customary Forests in the Research Environment of Eastern Sabuai Seram Village.Methods of the Research: The approach method used in this study is sociological juridical which is a descriptive study of qualitative analysis. This study seeks to illustrate what is happening in the Indigenous peoples of Sabuai Village, SBT. The data collection techniques used in this study were: Interviews, questionnaires and literature studies.Results of the Research: The form of cv accountability of the source of prosperous blessings that encroached on customary forests in Sabuai Village, Eastern Seram Regency, namely: From the point of view of administrative law, permission is a public service. In fact, permits as one of the sources of destruction and pollution in the name of illegal logging, illegal fissing and illegal maning. Thus illegal logging is a fraudulent practice since from licensing, activities, results of activities, actors and the purpose of their sale subscribe to the law. Legal liability under civil law in illegal encroachment is: The principle of liability based on unlawful acts, the Principle of absolute liability (strike liability) and the Principle of Liability based on Unlawful Acts.